PET Imaging of Serotonin Transporters with 4-[18F]-ADAM in a Parkinsonian Rat Model. Issue 7 (July 2013) - Weng, Shao-Ju; Shiue, Chyng-Yann; Huang, Wen-Sheng; Cheng, Cheng-Yi; Huang, San-Yuan; Li, I-Hsun; Tao, Chih-Chieh; Chou, Ta-Kai; Liao, Mei-Hsiu; Chang, Yung-Ping; Ma, Kuo-Hsing
This study was undertaken to address the effects of fetal mesencephalic tissue transplantation on the serotonin system in a rat model of Parkinson's disease (PD) while also investigating the usefulness of 4-[ 18 F]-ADAM (a serotonin transporter imaging agent) coupled with micro-PET for imaging serotonin transporters (SERTs). A PD model was induced by unilateral injection of 6-hydroxydopamine (6-OHDA) into the right medial forebrain bundle of the nigrostriatal pathway, while cell transplantation was performed via intrastriatal injection of mesencephalic brain tissue dissected from embryonic (E14) rats. The 4-[ 18 F]-ADAM/micro-PET scanning was performed following both 6-OHDA lesioning and transplantation. Immunohistochemistry (IHC) studies were also performed following the final PET scan, and the results were compared to show a 17–43% decrease in the specific uptake ratio (SUR) and a 23–52% decrease in serotonin transporter immunoreactivity (SERT-ir) within various brain regions on the lesioned side. The number of methamphetamine-induced rotations also decreased significantly at the 4th week postgraft. In addition, striatal SUR and the SERT-ir levels were restored to 77% and 83% 5 weeks postgraft. These results suggest that Parkinson's disease also affects the serotonergic system, while both the dopaminergic and serotonergic systems can be partially restored in a rat model of PD after E14 mesencephalic tissue transplantation. In addition, we have also determined that 4-[ 18 F]-ADAM/micro-PET can be used to detect serotonergic neuron loss, monitor the progress of Parkinson's disease, and oversee the effectiveness of therapy.